Does culture shape face perception in autism? Cross‐cultural evidence of the own‐race advantage from the UK and Japan. Issue 5 (11th February 2020) - Hanley, Mary; Riby, Deborah M.; Derges, Michael‐John; Douligeri, Anna; Philyaw, Zackary; Ikeda, Takahiro; Monden, Yukifumi; Shimoizumi, Hideo; Yamagata, Takanori; Hirai, Masahiro
Abstract: Autism spectrum disorders (ASD) are associated with face perception atypicalities, and atypical experience with faces has been proposed as an underlying explanation. Studying the own‐race advantage (ORA) for face recognition can reveal the effect of experience on face perception in ASD, although the small number of studies in the area present mixed findings. This study probed the ORA in ASD by comparing two cultural groups simultaneously for the first time. Children with ASD in the UK ( N  = 16) and Japan ( N  = 26) were compared with age‐ and ability‐matched typically developing (TD) children in the UK ( N  = 16) and Japan ( N  = 26). Participants completed a two‐alternative forced‐choice task, whereby they had to recognize a just seen face from a foil which was manipulated in one of four ways (IC: identity change; EE: easy eyes; HE: hard eyes; HM: hard mouth). Face stimuli were Asian and Caucasian, and thus the same stimuli were own and other race depending on the cultural group. The ASD groups in the UK and Japan did not show impaired face recognition abilities, or impairments with recognizing faces depending on manipulations to the eye region, and importantly they showed an ORA. There was considerable heterogeneity in the presence of the ORA in ASD and TD and also across cultures. Children in Japan had higher accuracy than children in the UK, and TD children in Japan did not show an ORA. This cross‐cultural study challenges the view that atypical experiences with faces lead to a reduced/absent ORA in ASD. Abstract : There is considerable heterogeneity in the presence of an own‐race advantage (ORA) in both typical development and in those with an autism spectrum diagnosis. There is also vast heterogeneity in the extent of an ORA between participants in the UK and in Japan. The current cross‐cultural study challenges the view that atypical experiences with faces lead to a reduced or absent ORA in children with autism.